Clinical Risk Index Score (CRIB II) as a Predictor of Neonatal Mortality among Premature Babies - Sadia Qasim, Sehar Zahid, Ashbah Islam, Muhammad Anwar, Shahzia Siddique, Arshad Rafique, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine predictive accuracy of CRIB II score in predicting mortality among premature with low birth weight neonates. Study design: Cross-sectional study. Place and duration of study: Paediatric NICU, Services Hospital Lahore from 2nd June 2017 to 2nd December 2017. Methodology: Two hundred and forty preterm new-born born before 32 weeks and birth weight from 600-1500grams were enrolled. Temperature was measured using rectal thermometer. Arterial blood gas sample was taken using standard sampling technique for base excess. Premature infants were evaluated for CRIB-II Score within 1 hour of arrival. Neonates were followed for 28 days to assess for their survival status. Results: The mean CRIB-II score was 10.95±2.79, mean gestational age was 29.16±1.58 weeks and mean weight was 1111.13±202.28 grams. There were 123(51.25%) males and 117(48.75%) were females. Actual neonatal mortality was 82(34.17%). Predictive accuracy of CRIB II score in predicting mortality among premature and very low birth weight neonates admitted to NICU was 92.68% for sensitivity, 94.94% specificity, 90.48% positive predictive value and 96.15% had negative predictive value. Conclusion: The predictive accuracy of CRIB II score is higher in prediction of mortality among premature and very low birth weight neonates. Keywords: Neonates, Premature, Very low birth weight, Mortality, CRIB II score, Prediction